2015
DOI: 10.1177/1759091414568185
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Facts in Multiple Sclerosis

Abstract: The question whether dietary habits and lifestyle have influence on the course of multiple sclerosis (MS) is still a matter of debate, and at present, MS therapy is not associated with any information on diet and lifestyle. Here we show that dietary factors and lifestyle may exacerbate or ameliorate MS symptoms by modulating the inflammatory status of the disease both in relapsing-remitting MS and in primary-progressive MS. This is achieved by controlling both the metabolic and inflammatory pathways in the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
197
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(204 citation statements)
references
References 165 publications
(184 reference statements)
1
197
0
6
Order By: Relevance
“…Our study on the more common delayed immune responses, IgG+IgA, illustrates a need for some individuals to abstain from consuming dairy products. To improve clinical conditions, the dairy-free diet has been recommended for patients with nephrotic syndrome [59], osteoarthritis [60], diabetes [61,62], and neurological disorders [63,64]. Indeed, dairy protein antibodies have been shown to cross-react with glutamic acid decarboxylase (GAD)-65 [22], GAD-67, and insulin receptor-α [65], an important serological marker for type 1 diabetes and latent autoimmune diabetes in adults (LADA) [66].…”
Section: Discussionmentioning
confidence: 99%
“…Our study on the more common delayed immune responses, IgG+IgA, illustrates a need for some individuals to abstain from consuming dairy products. To improve clinical conditions, the dairy-free diet has been recommended for patients with nephrotic syndrome [59], osteoarthritis [60], diabetes [61,62], and neurological disorders [63,64]. Indeed, dairy protein antibodies have been shown to cross-react with glutamic acid decarboxylase (GAD)-65 [22], GAD-67, and insulin receptor-α [65], an important serological marker for type 1 diabetes and latent autoimmune diabetes in adults (LADA) [66].…”
Section: Discussionmentioning
confidence: 99%
“…This partial failure may be due to the fact that MS is a complex and multifactorial disease. In fact, in addition to the genetic and immunological components, various environmental and/or metabolic factors or conditions may have a role in its development: i) viral infections, [12][13][14] ii) heavy metal poisoning, 15,16 iii) smoking, 14,17 iv) childhood obesity, 18 v) incorrect life style, mostly including wrong dietary habits, 19,20 or vi) low vitamin D status. 21 The most significant difference between the different causative agents listed above is that, unlike the others, dietary habits and lifestyle (v) and vitamin D levels (vi) can be modified to provide beneficial effects on the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Fish oil and n-3 PUFA inhibit the pro-inflammatory transcription factor nuclear transcription factor-kB (NF-kB) and lower the level of the gelatinase B, also known as matrix metalloproteinase-9 (MMP-9) (another important mediator of inflammation). 20,25,26,34 In addition, n-3 PUFA have neuroprotective properties and may be very useful in the complementary treatment in MS patients. DHA is present at high concentration in the brain and its levels decreases dramatically in MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Several studies have shown that both anti-MS-specific therapies [6][7][8][9] and some antioxidant and anti-inflammatory compounds have the ability to downregulate MMPs, suggesting that inhibition of MMPs may represent an additional mechanism by which these agents decrease the development of new CNS lesions in the course of MS. [10][11][12] In this review, we summarize the general characteristics of the different MMPs and their regulatory mechanisms. The pathogenic role of MMPs in the development and progression …”
Section: Introductionmentioning
confidence: 99%